Two new species of Scottmoria (Lecythidaceae) from western Ecuador and six new combinations in the genus - Cornejo, Xavier; Prance, Ghillean T. (Phytotaxa, 2025)
Two new species of neotropical Lecythidaceae from western Ecuador are formally described: Scottmoria austroccidentalis from montane Andean forests in the El Oro Province, in southwestern Ecuador, and S. petalocostata from the Andean slopes of the Carchi Province, in northwestern Ecuador. Also, six new combinations are formally presented, which were transferred from Eschweilera to Scottmoria: Scottmoria beebei (Pittier ex S.A. Mori) Prance, S. bogotensis (R. Knuth) Cornejo & Prance, S. garagarae (Pittier) Cornejo & Prance, S. integricalyx (S.A. Mori) Cornejo & Prance, S. microcalyx (S.A. Mori) Prance & Cornejo, and S. venezuelica (S.A. Mori) Prance. The new species are illustrated and the morphological differences with related species are discussed.